Relation of BMI and Body Fat Percentage with Nutritional Status of Adolescents - D. Godia, Dr. Haresh; Nikam, Dr. Lalit H (International Journal of Innovative Research in Medical Science, 2018)
Aims: Relation of BMI and Body Fat Percentage with Nutritional Status of Adolescents in first year medical students. Materials and Methods: Study was carried out in Tertiary Care Hospital and Seth G S Medical College Parel Mumbai. 100 1st year M.B.B.S. students were selected for study group contains 50 males and 50 females. Studies carried out on adolescents are very limited and it is needed to assess the nutritional status of adolescents. An attempt has therefore been made in the present study to Conclusion: From the present study it is concluded that 72% of females and 78% of males are well nourished; 8% of females and 6% of males are over nourished and 20% of females and 16% of males are under-nourished. Considering the consequences or morbidity and mortality associated with undernourishment; corrective steps in the form of improvement in dietary pattern should be undertaken and for over-nourishment; in addition to rectification of diet, more stress should also be laid on doing physical activity. For Adolescent: BMI- Cutt off points as suggested by WHO should be followed rather than following the adult BMI values as the adult BMI value give a high estimate prevalence of malnutrition.